Developing a model of landscape elements in residential open spaces effective on social resilience (Comparative study of Basmayeh & Haifa residential open spaces in Baghdad, Iraq) - Alboadam, Hasan Shakir; KhakZand, Mehdi (Edelweiss Applied Science and Technology, 2025)
This study explores the role of landscape elements in residential open spaces and their impact on fostering social resilience. By comparing Basmayeh, a modern planned community, and Haifa, an area characterized by vernacular architecture in Baghdad, Iraq, the research aims to develop a model of effective landscape design. Using surveys, field observations, and community feedback, the study examines how design elements influence social interaction, mental well-being, inclusivity, and community identity. Results show that modern open spaces prioritize recreation and aesthetics, while vernacular spaces emphasize social cohesion and cultural heritage. The study concludes with a hybrid model integrating the strengths of both contexts to create inclusive, resilient residential open spaces. Recommendations include adopting context-sensitive designs, enhancing accessibility, and promoting community participation in the design process.